L’orto di Eugetus, gli innesti del Cuperus ed un ramoscello scomparso (Luxor. 332 Happ) - PAOLUCCI, Paola (AL. Rivista di studi di Anthologia Latina, 2021)
Abstract After some considerations about Cuperus’ copy of the epigram by Luxorius 332 Happ, a correction of v. 7 Laconides is given.